Impact of Leave-on Skin Care Products on the Preservation of Skin Microbiome: An Exploration of Ecobiological Approach - Callejon S; Giraud F; Larue F; Buisson A; Mateos L; Grare L; Guyoux A; Perrier E; Ardiet N; Trompezinski S (Clinical, Cosmetic and Investigational Dermatology, 2023)
Sylvie Callejon,1,2 Félix Giraud,1,2 Florence Larue,1 Armonie Buisson,1 Léa Mateos,1,2 Laurence Grare,1 Aurélie Guyoux,1 Eric Perrier,2 Nathalie Ardiet,1 Sandra Trompezinski1,2 1NAOS Group, Research and Development Department, Aix-en-Provence, France; 2NAOS Institute of Life Science, Aix-en-Provence, FranceCorrespondence: Sandra Trompezinski, 355 Rue Pierre Simon Laplace, 13593 Aix-en-Provence Cedex 03, Aix-en-Provence, France, Tel +33 4 42 60 73 65, Email sandra.trompezinski@naos.comPurpose: Skincare products are used daily to maintain a healthy skin, although their skin microbiome impact is still poorly known. Preserving the natural resources and mechanisms of the skin ecosystem is essential, and a novel approach based on these premises, called ecobiology, has recently emerged in skincare. We evaluated the impact on the skin microbiome of three types of leave-on face skincare products: a hydrophilic solution, a micellar solution, and an oil-in-water emulsion.Patients and Methods: Samples for microbial profiling were obtained from 20 Caucasian females twenty-four hours and four days following daily application of the skincare products and compared to an untreated area. The bacterial diversity and the abundance of the skin microbiome were analyzed by 16S rRNA gene sequencing using an Illumina MiSeq platform.Results: Our results confirmed the skin microbiome diversity and the prevalence of Cutibacterium spp. and Staphylococcus spp. at sebaceous sites. The bacterial diversity and abundance were not affected by the products, and no dissimilarities versus the control nor between each product were noted at both times.Conclusion: These preliminary results demonstrate for the first time that three types of leave-on face skincare products have no impact on the human skin microbiome and can be considered to be “microbiome friendly”.Keywords: cosmetic product, ecobiology, microbiome friendly